2021
DOI: 10.1038/s41598-021-84536-8
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial on the effects induced by robot-assisted and usual-care rehabilitation on upper limb muscle synergies in post-stroke subjects

Abstract: Muscle synergies are hypothesized to reflect connections among motoneurons in the spinal cord activated by central commands and sensory feedback. Robotic rehabilitation of upper limb in post-stroke subjects has shown promising results in terms of improvement of arm function and motor control achieved by reassembling muscle synergies into a set more similar to that of healthy people. However, in stroke survivors the potentially neurophysiological changes induced by robot-mediated learning versus usual care have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 56 publications
3
40
0
1
Order By: Relevance
“…However, it is not yet clear which are the rehabilitative goals in terms of muscle coordination—for example, whether to promote muscle synergies resembling the ones of healthy individuals or new ones [ 95 , 96 ]. Preliminary evidence in acute stroke patients suggests that during motor recovery, altered muscle synergies tend to resemble the ones of healthy individuals [ 23 , 97 ]. This could be taken into account, further explored and exploited in robot-based rehabilitation protocols to maximize functional recovery after neurological injuries and better enable rehabilitation professionals to devise treatment plans based on the residual individual abilities.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not yet clear which are the rehabilitative goals in terms of muscle coordination—for example, whether to promote muscle synergies resembling the ones of healthy individuals or new ones [ 95 , 96 ]. Preliminary evidence in acute stroke patients suggests that during motor recovery, altered muscle synergies tend to resemble the ones of healthy individuals [ 23 , 97 ]. This could be taken into account, further explored and exploited in robot-based rehabilitation protocols to maximize functional recovery after neurological injuries and better enable rehabilitation professionals to devise treatment plans based on the residual individual abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Definition: A MSyn is a model that reduces the dimensionality of muscle control, by decomposing the activation of a group of muscles to produce a particular movement (Bizzi and Cheung, 2013;Overduin et al, 2015) Measurement: MSyn are generally addressed by applying linear decomposition algorithms (PCA, NNMF, and ICA) to extract spatiotemporal, temporal, and spatial features from EMG (Grinyagin et al, 2005) State of the art: Although MSyn are being widely explored as neuromechanical models for robotic control, there is a current discussion about whether: (1) MSyn have a neural origin, (2) are encoded in the central nervous system, (3) are activated because of task constraints (Severini et al, 2020) Comment on current/potential applications: Changes in MSyn after post-stroke robot-assisted rehabilitation showed larger improvements in axial-to-proximal muscle synergies with respect to usual care rehabilitation (Lencioni et al, 2021). Measurement of the temporal correlation between the recruitment of MSyn of paretic and healthy muscles on post-stroke survivors shows correlation of these synergy-based measures with clinical scores, and is proposed as a physiological biomarker of motor function and recovery in stroke, called Functional Synergy Recruitment Index (Irastorza-Landa et al, 2021)…”
Section: Muscular Synergies (Msyn)mentioning
confidence: 99%
“…Some other studies showed that muscle synergies and clinical scales were weakly correlated, and that stroke does not affect the inner structure of synergies, but rather their temporal recruitment [ 20 , 21 ]. There has also been evidence that synergies can improve in terms of their timing and organization by specific targeted therapies, including robot therapy or virtual reality treatment [ 15 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%